New guidelines for cardiopulmonary resuscitation Nuevas directrices para la resucitación cardiopulmonar Novas diretrizes da ressuscitação cardiopulmonar - Maria Celia Barcellos Dalri; Izilda Esmenia Muglia Araújo; Renata Cristina de Campos Pereira Silveira; Silvia Rita Marin da Silva Canini; Regilene Molina Zacareli Cyrillo (Universidade de São Paulo, 2008)
Cardiopulmonary arrest (CPA) poses a severe threat to life; cardiopulmonary resuscitation (CPR) represents a challenge for research and assessment by nurses and their team. This study presents the most recent international recommendations for care in case of cardiopulmonary heart arrest, based on the 2005 Guidelines by the American Heart Association (AHA). These CPR guidelines are based on a large-scale review process, organized by the International Liaison Committee on Resuscitation (ILCOR). High-quality basic and advanced CPR maneuvers can save lives. La parada cardiorrespiratoria (PCR) es una ocurrencia que presenta una grave amenaza a la vida; la resucitación cardiopulmonar (RCP) representa un desafío para la investigación y la evaluación por parte del enfermero y su equipo. Este estudio presenta las más recientes recomendaciones internacionales sobre la atención a la parada cardiorrespiratoria, basada en las Directrices de 2005 de la American Heart Asociation (AHA). Esas directrices sobre RCP se fundamentan en un proceso de revisión extenso, organizado por el International Liasion Committee on Resuscitation (ILCOR). Las maniobras básicas y avanzadas de RCP ofrecidas con calidad pueden salvar vidas. A parada cardiorrespiratória (PCR) é intercorrência de grave ameaça à vida; a ressuscitação cardiopulmonar (RCP) representa desafio para a investigação e a avaliação por parte do enfermeiro e sua equipe. Esse estudo apresenta as mais recentes recomendações internacionais sobre atendimento da parada cardiorrespiratória, baseado nas Diretrizes de 2005 da American Heart Association (AHA). Essas diretrizes sobre RCP fundamentam-se num processo de revisão extenso, organizado pelo International Liasion Committee on Resuscitation (ILCOR). As manobras básicas e avançadas de RCP com qualidade podem salvar vidas.